2005
DOI: 10.1074/jbc.m504807200
|View full text |Cite
|
Sign up to set email alerts
|

cDNA Cloning and Expression of the Cardiac Na+/Ca2+ Exchanger from Mozambique Tilapia (Oreochromis mossambicus) Reveal a Teleost Membrane Transporter with Mammalian Temperature Dependence

Abstract: The complete cDNA sequence of the tilapia cardiac Na ؉ /Ca 2؉ exchanger (NCX-TL1.0) was determined. The 3.1-kb transcript encodes a protein 957 amino acids in length, with a predicted signal peptide cleaved at residue 31 and two potential N-glycosylation sites in the extracellular N terminus. Hydropathy analysis and sequence comparison predicted a mature protein with nine transmembrane-spanning segments, consistent with the structural topologies of other known mammalian and teleost NCX isoforms. Overall sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 72 publications
0
8
0
1
Order By: Relevance
“…It has been recently demonstrated that NCX4 is expressed in the zebrafish [21] but characterization of its Na + /Ca 2+ exchange and tissue localization requires exploration. As for the duplicate NCX genes in teleosts, only one NCX1a from the zebrafish [19] and three NCX1b have been cloned and demonstrated to be functional in cardiac tissue in zebrafish [19], trout [17] and tilapia [18]. Zebrafish is the only teleost in which both NCX1 have been cloned from cardiac ( NCX1h/NCX1b ) [GenBank:AY934775] and neural tissues ( NCX1n/NCX1a ) [GenBank:AY934776] [19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been recently demonstrated that NCX4 is expressed in the zebrafish [21] but characterization of its Na + /Ca 2+ exchange and tissue localization requires exploration. As for the duplicate NCX genes in teleosts, only one NCX1a from the zebrafish [19] and three NCX1b have been cloned and demonstrated to be functional in cardiac tissue in zebrafish [19], trout [17] and tilapia [18]. Zebrafish is the only teleost in which both NCX1 have been cloned from cardiac ( NCX1h/NCX1b ) [GenBank:AY934775] and neural tissues ( NCX1n/NCX1a ) [GenBank:AY934776] [19].…”
Section: Resultsmentioning
confidence: 99%
“…Expression levels generally correlate with the perceived importance of transmembrane Ca 2+ flux in a particular cell type (i.e., high in cardiac, neuronal, and kidney tissue but relatively low in liver tissue). An NCX1 homolog has been cloned and characterized in several teleosts including trout [17], tilapia [18], and zebrafish [19]. We recently discovered a NCX gene ( NCX4 ) that has been found only in fish species [20].…”
Section: Introductionmentioning
confidence: 99%
“…This is especially true when one considers that the charge transferred by the L-type Ca 2+ channels given above was measured with 5·mmol·l -1 EGTA in the pipette solution, which augments Ca 2+ influx. Studies using non-teleost expression systems demonstrate that the trout NCX temperature-sensitivity is quite low (Q 10~1 .1) (Elias et al, 2001), whereas the NCX of a tropical fish species, the tilapia Oreochromis mossambicus, shows a similar temperature-sensitivity to mammals (Marshall et al, 2005). Surprisingly, the burbot I NCX shows a relatively strong temperature dependence (Q 10 =2.47) between 4°C and 11°C when recorded in native myocytes.…”
Section: Sarcolemmal Ca 2+ Transport In Burbot Ventricular Myocytesmentioning
confidence: 99%
“…Due to the limited availability of NCX functional studies with the giant patch clamp, our sequence and functional comparisons are valid for only a few NCX homologs. These include NCX2 from the human (13), NCX1 from the dog (3), NCX3 from the dog/human (unpublished data), NCX1b from rainbow trout (3), and NCX1b from tilapia (19). Within the ␣-1 domain, NCX4a had the highest identity (at the amino acid level) at ϳ90% with dog NCX1, human NCX2, and human/dog NCX3.…”
Section: Resultsmentioning
confidence: 99%